Comparison of short-term vs. long-term estrous synchronization protocols using CIDR devices in sheep and goats during and outside the natural breeding season - Harl, Audra Whitney (Kansas State University, 2014)
Controlling reproductive cycles during active cyclicity and seasonal anestrous in small ruminants is critical for profitability. The objective of this study was to evaluate the effect on estrous response and interval to estrus of two CIDR protocols in sheep and goats during breeding and non-breeding seasons. In experiment 1, 133 ewes were randomly assigned to 1 of 3 treatments during the breeding season. In the CIDR-7 group, ewes received a CIDR insert for 7 d. In the CIDR-7 + PGF treatment, ewes received a CIDR insert for 7 d and 20 mg of prostaglandin-F[subscript]2[subscript]α (PGF[subscript]2[subscript]α) upon CIDR removal. Ewes in the CIDR-14 treatment received a CIDR insert for 14 d. Following CIDR removal all ewes were exposed to a ram every 12 h until breeding. There was a shorter interval from CIDR removal to estrus in the CIDR-14 treatment compared to the CIDR-7 and CIDR-7 + PGF treatments (P<0.05). There was no difference in number of ewes per treatment displaying estrus. In experiment 2, 54 ewes were randomly assigned to one of two treatment groups during the anestrous season. Ewes in CIDR-7 and CIDR-14 treatments received a CIDR insert for 7 d and 14 d, respectively. Upon CIDR removal ewes were exposed to a ram every 12 h until breeding. There was a significantly shorter interval from CIDR removal to estrus in CIDR-14 ewes when compared with CIDR-7 ewes (P<0.05). For experiment 3, 37 Boer does were randomly assigned to one of two treatments. In the CIDR-10 treatment, does received a CIDR insert for 10 d and 20 mg of PGF[subscript]2[subscript]α at time of CIDR removal. In the CIDR-19 treatment, does received a CIDR insert for 19 d. Upon CIDR removal, does were exposed to a buck fitted with a marking harness and chalk marks were recorded every 12 h. The number of does displaying estrus was not different (CIDR-7, 85%; CIDR-14, 95%). There was no difference in interval from CIDR removal to estrus between treatments. Results from experiments 1 and 2 supported the hypothesis that long-term protocols yield a shorter interval to estrus when compared with short-term protocols.
Keywords: estrous synchronization; CIDR; anestrous; doe; ewe; Animal Sciences (0475)